Epithelial Cell Abnormality in Cervical Pap Smear with Histopathological Correlation among Patients of a Tertiary Care Centre in Eastern Nepal - Das, Manish Kumar; Bhandari, Rashmita (Journal of Nobel Medical College, 2022)
Background: Cervical cancer is a leading health problem among women all over the world with significant mortality and morbidity in developing countries like Nepal. Pap smear is an effective and cost efficient diagnostic technique for cervical lesions. This study aims at histopathological correlation of cervical Pap smears.Materials and Methods: A cross sectional study was conducted from January 2020 to January 2022 in Pathology department of Nobel Medical College Teaching Hospital (NMCTH). 119 cases of cervical Pap smear were reported using the Bethesda system and correlated with histopathological examination findings for various epithelial cell abnormalities. Analysis was done using SPSS software version 20.Results: Out of 5110 smears examined, 119 were positive for epithelial cell abnormalities. Cellular abnormality was commonly seen between 31-60 years of age. Low grade Squamous Intraepithelial Lesion was the commonest lesion found. Pap smear findings had good concordance rates with histopathological findings for individual lesions. The overall sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of Pap smear were 84%, 23.1%, 89.9%, 15% and 77.3% respectively.Conclusion: Pap smear has a good diagnostic accuracy, sensitivity and positive predictive value in diagnosing cervical lesions in comparison to histopathological examination